Direct Bone Formation during Distraction Osteogenesis does not require TNFα Receptors and Elevated Serum TNFα Fails to Inhibit Bone Formation in TNFR1 Deficient Mice - Wahl, Elizabeth C. (2009)
Distraction Osteogenesis (DO) is a process which induces direct new bone formation as a result of mechanical distraction. Tumor necrosis factor-α (TNF) is a cytokine that can modulate osteoblastogenesis. The direct effects of TNF on direct bone formation in rodents are hypothetically mediated through TNF receptor 1 and/or 2 (TNFR1/2) signaling. We utilized a unique model of mouse DO to assess the effects of 1) TNFR homozygous null gene alterations on direct bone formation and 2) rmTNF on wild type (WT), TNFR1 (-/-) (R1KO), and TNR2 (-/-) (R2KO) mice. Radiological and histological analyses of direct bone formation in the distraction gaps demonstrated no significant differences between the WT, R1KO, R2KO, or TNFR1 (-/-) & R2 (-/-) (R1&2KO) mice. R1&2KO mice had elevated levels of serum TNF but demonstrated no inhibition of new bone formation. Systemic administration by osmotic pump of rmTNF during DO (10 ug/ kg/day) resulted in significant inhibition of gap bone formation measures in WT and R2KO mice, but not in R1KO mice. We conclude that exogenous rmTNF and/or endogenous TNF act to inhibit new bone formation during DO by signaling primarily through TNFR1.